A Study of Academic Readiness of Preschool Children - YADAV, PADMA (THE PRIMARY TEACHER, 2014)
The present paper is based on a comparative study of the academic readiness of two groups of children of Class I – one exposed to the normal preschool programme and another exposed to early reading, writing and arithmetic experiences. The study was carried out to find out whether a preschool experience stressing early reading, writing and arithmetic would help children in early literacy and numeracy skills in Class I. The crucial importance of preschool and the need for preparing children, before they enter Class I and exposing them to a programme of preschool learning, is now universally recognised. The early childhood years especially 4 to 5 years age group in a preschool enable a child to think, to listen and to judge for themselves. Normally the teachers of Class I feel that a child with preschool experiences adjusts easily to the demands of Class I. The question here is whether the education that children get in the preschools is appropriate to their stage of development and needs, so as to lay a firm foundation for the future years. The preschool programme can and should bridge the gap that the child faces between her preschool years and her beginning of the primary school